Optimizing Manufacturing Technology: Unraveling Symmetry in Cubic Equation Roots - Černohlávek, Vít; Klimenda, František; Suszynski, Marcin; Štěrba, Jan; Zdráhal, Tomáš (Manufacturing Technology Journal, 2024)
In the realm of engineering the quest for optimization is ceaseless. This article explores the intricate relation-ship between cubic equations and the practical world of production technologies, unearthing the profound connections that underpin mathematical symmetry and its role in engineering. Cubic equations, often arising in the analysis of mechanical systems, electric circuits, and robotics, serve as indispensable tools for under-standing and enhancing real-world applications. This study delves into the methods for finding the roots of cubic equations, shedding light on the vital role of mathematics in engineering and manufacturing technology.
Keywords: Symmetry; Cubic equations; Symmetric polynomials; Manufacturing Technology; Optimization; Wolfram Mathematics